1991
DOI: 10.1152/jappl.1991.71.4.1574
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of oral breathing in lambs in response to airway obstruction: mechanisms

Abstract: Our aim was to assess the mechanisms determining the reflex formation of an oral airway in response to nasal obstruction (NO) and tracheal obstruction (TO). In nine conscious lambs (14-37 days old) NO was effected by blockade of nasal tubes; TO was later effected by blockade of an endotracheal tube. We measured arterial O2 saturation, PO2, PCO2, and pH and the depth and duration of inspiratory efforts when mouth opening (MO) occurred. Responses were compared when NO and TO followed breathing of room air, rebre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Thus, the signal received by the animal from airway mechanoreceptors, and the sense of inspiratory effort during obstructed inspiratory efforts, may have been stronger when nasal tubes were blocked. In accordance with our previous studies in conscious lambs (Harding et al 1991), our present findings in sleeping animals indicate that mechanical stimuli (or sense of effort) are of great importance in the initiation of responses to airflow obstruction. It is likely that the asphyxia that accompanies airflow obstruction will eventually cause arousal, but the latency for arousal will be shortened in the presence of mechanical stimuli which increase the intensity of inspiratory efforts.…”
Section: Comparison Of Responses To Nasal Obstruction With Responses supporting
confidence: 93%
See 3 more Smart Citations
“…Thus, the signal received by the animal from airway mechanoreceptors, and the sense of inspiratory effort during obstructed inspiratory efforts, may have been stronger when nasal tubes were blocked. In accordance with our previous studies in conscious lambs (Harding et al 1991), our present findings in sleeping animals indicate that mechanical stimuli (or sense of effort) are of great importance in the initiation of responses to airflow obstruction. It is likely that the asphyxia that accompanies airflow obstruction will eventually cause arousal, but the latency for arousal will be shortened in the presence of mechanical stimuli which increase the intensity of inspiratory efforts.…”
Section: Comparison Of Responses To Nasal Obstruction With Responses supporting
confidence: 93%
“…Respiratory responses to airflow obstruction during sleep were qualitatively similar to those observed previously in conscious lambs when the nasal airway was obstructed (Harding et al 1987(Harding et al , 1991; that is, there was an augmentation and slowing of inspiratory efforts. However, the magnitude of the increase in inspiratory efforts (in relation to the degree of hypoxaemia or duration of obstruction) was much greater in conscious lambs.…”
Section: Effects Of Sleep On Inspiratory Efforts During Airflow Obstrsupporting
confidence: 80%
See 2 more Smart Citations
“…One study has associated an increased nasal resistance with a tendency to use oral route breathing [21]; however, switching behaviour at rest has only been previously investigated in lambs [22], where complete nasal obstruction was required to induce oral breathing. The only study investigating breathing routes in asthmatic subjects demonstrated that, during an acute exacerbation of asthma, subjects breathed oronasally but switched to nasal breathing post-recovery [1].…”
Section: Nasal Inspiratory Threshold Loadingmentioning
confidence: 99%